Self-efficacy and health status improve after a wellness program in persons with multiple sclerosis. (1st June 2013) - Ng, Alexander; Kennedy, Patricia; Hutchinson, Brian; Ingram, Anna; Vondrell, Suzanne; Goodman, Terri; Miller, Deborah
Abstract : Purpose : To determine if an intensive wellness program for persons with MS results in improved self-efficacy, quality of life (QOL), or physical activity outcomes. Methods : 129 subjects participated in one of seven 4-day interdisciplinary educational wellness programs throughout the United States. This intervention was based on the philosophy that health management is important to disease management. The program consisted of psychological and physiological evaluations, lectures and workshops. Before the intervention and after at 1, 3 and 6 months, self-efficacy (MS Self-Efficacy Scale, MSSE, control), health related QOL (SF-36) and physical activity (Physical Activity Scale for Persons with Physical Disabilities, PASAID) was assessed. Results : Improvements were noted at 1, 3 and 6 months post-intervention. Those present at 6 months included, MSSE, role physical, vitality and mental health scales of the SF-36. PASAID did not change. Improvements were independent of disability (EDSS). Conclusion : A 4-day multidisciplinary educational wellness program can result in improvement in self-efficacy and health-related QOL in persons with MS and can be stable up to at least 6 months. Improvements do not depend on degree of disability.